(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
This article deals with the world view of ancient Kyrgyz people, the deep meaning of folk language devices kept untill nowadays, the prove of nomad peoples cognition value, nomad Kyrgyz peoples ethnic culture, as spiritual value examples used in mental phraseological words about their etimology and views in Linguistics. As cattle-breeding was nomadic peoples main profession, the phraseological words etimology were considered in this article. Furthermore, ancient Kyrgyz peoples principles of keeping humanity, values, friendship, justice and phraseological words about customs and traditions were proved with clear examples.The reluance of this article is to search the ancient nomadic Kyrgyz peoples phraseological words.